2008
DOI: 10.1176/ps.2008.59.11.1335
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Inmates Who Received a Diagnosis of Serious Mental Illness Upon Entry to New York State Prison

Abstract: This is a very high-need population for which correctional mental health services need to plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…These results are similar to those of other studies of prison populations. Some type of severe mental disorder was found in 15% of women and 5% of men in prisons in New York City [29], and in 17.7% of women and 7.8% of men in prisons in Florida, USA [30].…”
Section: Discussionmentioning
confidence: 97%
“…These results are similar to those of other studies of prison populations. Some type of severe mental disorder was found in 15% of women and 5% of men in prisons in New York City [29], and in 17.7% of women and 7.8% of men in prisons in Florida, USA [30].…”
Section: Discussionmentioning
confidence: 97%
“…Way, Sawyer, Lilly, Moffitt, and Stapholz (2008) examined all inmates admitted from May 17, 2007, to June 14, 2007, to a New York State prison ( N = 2,918). In that time period, 5.9% of the inmates were diagnosed with serious mental illness, 36% with a psychotic disorder, 13% with major depression, 31% with a bipolar disorder, and 19% with an unspecified mood disorder (Way, Sawyer, Lilly, Moffitt, & Stapholz, 2008).…”
Section: Mental Illness and Inmatesmentioning
confidence: 99%
“…Studies of U.S. prison populations have consistently found elevated rates of SMI relative to the population at large (Brink 2005;Diamond et al 2001;Fazel and Danesh 2002;Lamb and Weinberger 1998). Among individual studies, however, the rates of SMI have varied widely (Baillargeon et al 2000;Chiles et al 1990;Daniel et al 1988;Dvoskin and Steadman 1989;Good 1978;James and Glaze 2006;James et al 1980;Jordan et al 1996;Neighbors 1987;Powell et al 1997;Steadman et al 1987;Veysey and Bichler-Robertson 2002;Walters et al 1988;Way et al 2008). This variability is attributed primarily to differences in study designs and methods, including selection and sampling, assessment protocols, and diagnostic nomenclature (Brink 2005;Diamond et al 2001;Jemelka et al 1989;Pinta 2001).…”
Section: Serious Mental Illness In the Us Prison Populationmentioning
confidence: 99%
“…Although only a minority of studies have evaluated the prevalence of SMI in female prisoners (Daniel et al 1988;Good 1978;Jordan et al 1996;Way et al 2008), the preponderance of evidence suggests that incarcerated women are more likely than men to have a current diagnosis of a major psychiatric disorder, especially major depressive disorder (Brink 2005). A study of 2,918 inmates, including 212 women, admitted to a New York state prison in 2007 showed that 15% of the women were diagnosed with SMI compared with only 5% of the men (p \ .001) (Way et al 2008). Pinta (2001) estimated that roughly 18% of women in U.S. prisons have SMI (i.e., psychotic disorders, bipolar disorders, and major depressive disorder) compared with only 10% of male inmates.…”
Section: Serious Mental Illness In the Us Prison Populationmentioning
confidence: 99%